Which medication is more effective as a first‐line agent for status epilepticus, midazolam or lorazepam?. Issue 6 (June 2018) - Adam, Patricia; Kilby, Nicole
Abstract : EVIDENCE‐BASED ANSWER : In a mixed population of adults and children requiring prehospital treatment, intramuscular (IM) midazolam is more effective than intravenous (IV) lorazepam for cessation of seizures, prevention of hospitalization, and prevention of intensive care unit (ICU) admissions (SOR: B, 1 large RCT). However, in studies limited to children, midazolam (IV or IM) is equivalent to IV lorazepam for the same outcomes (SOR: B, 2 small RCTs). IM midazolam is recommended in adults without pre‐established IV access, but either midazolam or lorazepam are appropriate in other situations (SOR: C, expert opinion).